PERLINDUNGAN HUKUM BAGI PENJUAL DALAM PERJANJIAN JUAL BELI KOMODITI AGRO DI PASAR LELANG FORWARD DI DAERAH ISTIMEWA YOGYAKARTA - Heriyani, Endang; Yuniarlin, Prihati (Jurnal Media Hukum, 2010)
The study on legal protection for Seller in Purchase Agreement of Agro Commodity in Auction Market in Special Territory of Yogyakarta was a normative and sociological legal research. This study aimed at knowing how the purchase agreement of agro commodity in forward auction market was applied, and how the legal protection for seller in purchase agreement of agro commodity in forward auction market was. The data used were secondary and primary data. The result of the study showed that the purchase of agro commodity in forward auction market. Legal protection for seller in purchase agreement of agro commodity in forward auction market was acquired from 3 (three) things: (a) The legal protection given by government, it was given through the legislation by the issue of the Decree of Ministry of Industry and Trade of Republic of Indonesia Number 650/MPP/Kep/10/2004 on terms of Operation of Auction Market with Forward Transfer of Agro Commodity. (b) The legal protection from the purchase agreement of agro commodity, the agreement made by the parties applied as the law for all parties; and (c) The legal protection in dispute, the problem was solved by a discussion. If the discussion made no result, arbitration would be done. Key Words: legal protection, purchase of agro commodity, forward auction market.